1990
DOI: 10.1200/jco.1990.8.11.1907
|View full text |Cite
|
Sign up to set email alerts
|

An early phase II study of CPT-11: a new derivative of camptothecin, for the treatment of leukemia and lymphoma.

Abstract: An early phase II study of a new camptothecin analog and an inhibitor of topoisomerase I, CPT-11, was conducted in 62 patients with refractory leukemia and lymphoma by four different treatment schedules in a multiinstitutional cooperative study. CPT-11 therapy resulted in four complete remissions (CRs) and three partial remissions (PRs) in 29 assessable non-Hodgkin's lymphoma (NHL) patients, one PR in three Hodgkin's disease (HD), one CR and one PR in 11 acute lymphoblastic leukemia (ALL), and one PR in 15 acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(61 citation statements)
references
References 9 publications
1
60
0
Order By: Relevance
“…Irinotecan (CPT-11) is a water-soluble camptothecin derivative that targets DNA topoisomerase I. CPT-11 has shown a strong anti-tumour activity as a single agent against a broad spectrum of experimental tumours (Kunimoto et al, 1987;Matsuzaki et al, 1988) as well as against various human malignancies including lung cancer (Ohno et al, 1990;Negoro et al, 1991b;Tacheuchi et al, 1991;Fukuoka et al, 1992; Masuda et al, 1992a;Shimada et al, 1993).…”
mentioning
confidence: 99%
“…Irinotecan (CPT-11) is a water-soluble camptothecin derivative that targets DNA topoisomerase I. CPT-11 has shown a strong anti-tumour activity as a single agent against a broad spectrum of experimental tumours (Kunimoto et al, 1987;Matsuzaki et al, 1988) as well as against various human malignancies including lung cancer (Ohno et al, 1990;Negoro et al, 1991b;Tacheuchi et al, 1991;Fukuoka et al, 1992; Masuda et al, 1992a;Shimada et al, 1993).…”
mentioning
confidence: 99%
“…Irinotecan has shown a good response in patients with relapsed and/or refractory malignant lymphoma (4)(5)(6). With regard to therapeutic efficacy of irinotecan in patients CPT-1 1 and Hodgkin's Lymphoma with Hodgkin's lymphoma, there is little information.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have shown that irinotecan has beneficial effects in patients with malignant lymphoma, especially relapsed and/or refractory nonHodgkin's lymphoma (4)(5)(6). However, the dose and schedule are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1A), a CM-Dex-PA adduct of the antineoplastic agent, 2,3,9,12,4′:6,7]The carboxymethylated polyalcohol is covalently bonded to the DX-8951 moiety via a tetrapeptidyl spacer (Gly-Gly-Phe-Gly, GGFG). DX-8951f (Fig.…”
mentioning
confidence: 99%